Fire robots. The main terms and definitions - Potekha Алексей Валентинович; Potekha Валентин Леонидович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
With use of system representations designs and methods of use of robotized systems of fire extinguishing are analyzed. The system of terms and the definitions describing the maintenance of a new direction in modem engineering of fire extinguishing is offered.